2018
DOI: 10.1051/0004-6361/201833276
|View full text |Cite
|
Sign up to set email alerts
|

Observations of solar chromospheric heating at sub-arcsec spatial resolution

Abstract: A wide variety of phenomena such as gentle but persistent brightening, dynamic slender features (∼100 km), and compact (∼1 ) ultraviolet (UV) bursts are associated with the heating of the solar chromosphere. High spatio-temporal resolution is required to capture the finer details of the likely magnetic reconnection-driven, rapidly evolving bursts. Such observations are also needed to reveal their similarities to large-scale flares, which are also thought to be reconnection driven, and more generally their role… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…4.4), and EBs will be prime targets that offer the opportunity to study the reconnection process in unprecedented detail. A very recent study of a UV burst at 75 km resolution (Smitha et al 2018) with the Ca II H line from the SUNRISE observatory suggests bursts may have a complex, flare-like structure when observed at ultra-high resolution.…”
Section: Discussionmentioning
confidence: 99%
“…4.4), and EBs will be prime targets that offer the opportunity to study the reconnection process in unprecedented detail. A very recent study of a UV burst at 75 km resolution (Smitha et al 2018) with the Ca II H line from the SUNRISE observatory suggests bursts may have a complex, flare-like structure when observed at ultra-high resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Since the ratio of their filter responses peaks sharply at around 1550 Å, the intensity ratio of the 1600 Å to 1700 Å filters (henceforth, UV ratio) traces the signal mostly from the C iv doublet. Signatures of UV bursts and rapid moss variability in the lower atmosphere can be traced in these UV ratio maps (Chitta et al 2018;Smitha et al 2018). We use these UV ratio maps in the second step to identify the footpoints of hot loops in the lower atmosphere.…”
Section: Observations and Methodsmentioning
confidence: 99%
“…UVBs (Peter et al 2014) are compact transient brightenings observed in UV bands, with very complex Si iv profiles, and do not generally show a co-spatial brightening in the coronal channels of the Solar Dynamics Observatory (SDO) Atmospheric Imaging Assembly (AIA) instrument. Similar targets have been studied with recent simulations (Danilovic 2017;Hansteen et al 2017Hansteen et al , 2019Libbrecht et al 2020) and observations (Socas-Navarro et al 2006;Toriumi et al 2017;Libbrecht et al 2017;Guglielmino et al 2018;Smitha et al 2018;Vissers et al 2019;Yadav et al 2019;Ortiz et al 2020;da Silva Santos et al 2020). Microflares or stronger events show a visible response in coronal channels and they would originate from or extend into higher layers.…”
Section: Introductionmentioning
confidence: 62%
“…Bi-directional flows at these locations are commonly reported in both observations and simulations (Peter et al 2014;Vissers et al 2019;Hansteen et al 2017). They usually have time scales of a few minutes (Vissers et al 2019;Smitha et al 2018), however, they can live up to several hours (Guglielmino et al 2018;Chitta et al 2017). Therefore, differences in their lifetime, size, location, etc., are used to distinguish them.…”
Section: Introductionmentioning
confidence: 98%